Role of Vitamin A and Vitamin D in management of polycystic ovary syndrome - Vindhya, M.; Bhumika, S.; Mythreyi, R.; Murugesan, Karthikeyan; Swamy, G. G.; Kandaswamy, Deepa; Valliyappan, Jayabalan; Elango, Boojhana; Basalingappa, Kanthesh M.; Mathanmohun, Maghimaa (Journal of Medicine and Health Sciences Research, 2023)
Polycystic ovarian syndrome (PCOS), a very common cause of infertility in reproductive age groups, has increased exponentially in the past few years registering 9% of cases annually worldwide. It is one of the most common syndromes which manifests hormone secretion and its activity. Insulin resistance, obesity, Vitamin and mineral deficiency, etc., are commonly associated with PCOS. Vitamin A is a lipid-soluble vitamin that is useful in antioxidant activity and steroid synthesis is known to prevent the occurrence of PCOS. Vitamin D, a steroid hormone originating from cholesterol is commonly known as “the sunshine vitamin,” is also one of the observed vitamin deficiencies in PCOS women. Supplementation of Vitamins in the diet is essential in the management of PCOS women. This review attempts to brief the role of Vitamin A and Vitamin D as an important agent to overcome the challenges of PCOS by reviewing the investigations of various authors about the potential role of supplementation of Vitamin A and Vitamin D in various model organisms and Randomised Clinical Trials (RCT’s).